2021
DOI: 10.1155/2021/3896130
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Mine Geological Environment Monitoring and Risk Assessment in Arid and Semiarid Areas

Abstract: Along with the accelerated shift of coal mining to the ecologically fragile west, the contradiction between coal resource development and ecological protection in the western arid and semiarid coal mining areas is rapidly intensifying. Based on the above background, this thesis takes the coal mining area in the arid and semiarid regions as an example; applies the theories of ecology, coal mining subsidence, geodesy, and ecological restoration; uses remote sensing in synthetic aperture radar (SAR), geographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…It is well-known that the uncertainty of random variables will greatly afect the output response. It is important for engineering risk assessment to determine the infuence of the uncertainty of random variables on output response [1]. Tere are many uncertainties in the actual slope engineering, so it is important to study these uncertainties for slope stability.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the uncertainty of random variables will greatly afect the output response. It is important for engineering risk assessment to determine the infuence of the uncertainty of random variables on output response [1]. Tere are many uncertainties in the actual slope engineering, so it is important to study these uncertainties for slope stability.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that 0.22 hm 2 of land is destroyed for every 10,000 tons of coal produced through opencast mining (Lechner et al, 2016). In addition, coal exploitation can lead to widespread ground fissures (Yang et al, 2022), rapid decrease of forest resources and grassland (Wu et al, 2021), expose polycyclic aromatic hydrocarbons (PAhs) to the ecological environment (Jiang et al, 2022), and intensify soil erosion and desertification (Jin et al, 2021), which can lead to ecological destruction in the mining area. Many large-scale coal mines in China are located in semiarid and arid regions, where the ecology and environment are easily degraded by mining activities (Pasture, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous development of underground coal mining would lead to the deformation and collapse of the overlying strata, resulting in fissures and subsidence, which will destroy the groundwater aquifer system [6], reduce the regional groundwater level, and affect the surface ecological environment. Unlike other regions, coal deposits in Inner Mongolia and Shaanxi are located in arid and semi-arid regions [7][8][9], which are areas of serious soil erosion in China, and their ecological environment is very fragile. Consequently, there is a major contradiction between groundwater loss through drainage by coal mining and the lack of water resources for vegetation growth.…”
Section: Introductionmentioning
confidence: 99%